Perencanaan Sistem PLTS Off-Grid Untuk Kebutuhan Energi Listrik Pada Perkebunan Kelapa Sawit - Peprizal, Peprizal; Maulana, Ade Putra; Jasman Duli, Sirlus Andreanto; Faristasari, Evvin; Hero Istoto, Enggar (Jurnal Inovasi Teknologi Terapan, 2025)
Palm oil plantations are one of the important sectors in the growth of the economy in Indonesia. One of the palm oil plantation areas in the Pasaman Barat Regency is being developed with an estimated land area of 100 hectares. However, due to the location of the land being far from settlements, there is currently no electricity supply that can be used for the operational needs of the land. This research provides a solution for the planning of an Off-Grid solar power plant (PLTS). The method used is a descriptive method with a quantitative research type. Based on the calculations, the number of PV panels obtained was 14 units and produces a total power of 2.397,89 W, SCC capacity calculation obtained 35 A, Battery capacity 12V/100Ah 2 units, and inverter 3 kW to produce AC voltage. The calculation of the Bill of Quantities (BoQ) for material needs amounts to Rp. 21.986.000. This result indicates that the planning of the solar power system is feasible for the long-term operational needs of the plantation, which only requires initial construction capital.